Abscisic acid alleviates chilling injury in cold-stored peach fruit by regulating ethylene and hydrogen peroxide metabolism - Tang, Jixing; Zhao, Yaoyao; Qi, Shuning; Dai, Qi; Lin, Qiong; Duan, Yuquan (Frontiers in Plant Science, 2022)
Peach (Prunus persica (L.) Batsch) is susceptible to chilling injury under improper low-temperature storage (2°C–5°C). Previous research has shown that abscisic acid (ABA) alleviates chilling injury in fruits and vegetables, but the potential mechanism is still unclear. To explore its effectiveness and potential mechanism in alleviating chilling injury during cold storage, exogenous ABA was applied to peach fruit by immersion in 100 μmol L−1 solutions for 10 min. In our experiment, ABA alleviated chilling injury by reducing hydrogen peroxide (H2O2) content and ethylene production. In addition, ABA inhibited the expression of the ethylene synthesis-related genes PpACO1 and PpEIN2. At the same time, ABA activated the antioxidant enzymatic pathway and the ascorbate-glutathione (AsA-GSH) cycle, the transcript abundance encoding genes related to antioxidant enzyme activities also changed correspondingly. The results suggested that ABA alleviated chilling injury by scavenging excessive H2O2 by promoting antioxidant enzymes and the AsA-GSH pathway.